Study of changes in maximum temperature and summer heat waves characteristics in Syrian coastal region during the period 1977-2016 - ميشيل سكاف; ليال رنجوس (Latakia University Journal -Biological Sciences Series, 2022)
Climate change one of the grand challenges facing societies and natural ecosystems worldwide, especially in Mediterranean regions which considered as climate change’s hot spots. Daily and monthly meteorological data for maximum temperature were used to detect changes in seasonal and annual mean of maximum temperature and to evaluate changes in heat waves number, duration and frequency for three meteorological stations (Latakia , Safita and Tartous) located in Syrian coastal region during the period 1977-2016. Heat wave was identified as the period of three consecutive days or more with maximum temperature above 30°c . Box- plots with coefficient of variation were used to illustrate monthly maximum temperature characteristics in coastal region. Trends with Mann-Kendall test were applied to detect significant changes in mean, maximum temperature at annual and seasonal time scales and to detect changes in heat waves number, duration and frequency. Descriptive analysis with T-test was used for comparison of two periods 1977-1996 and 1997-2016. Results showed increasing tendency in annual maximum temperature related to significant increase in mean maximum temperature in all seasons especially in summer, and this increase led to significant changes in heat waves number, duration, and frequency, which increased in all stations during the studied period. These changes in maximum temperature and related increase in heat waves number and duration will pose a big threats to human health, water resources, agriculture production and natural ecosystems.